Sacrococcygeal Pilonidal Sinus: A Comparative Study of Excision with Laying Open and Bascom's Technique - Lateef Naif Razeek; Hussein Sahan Jasim; Esam Abdalhameed Hasan (Zien Journals, 2022)
Pilonidal Sinus is a disease that most commonly arises in the hair follicles of the natal cleft of the sacrococcygeal area of young adults. Principles of treatment require eradication of the sinus tract; complete healing of the overlying skin and prevention of recurrence
Keywords: Pilonidal sinus; Excision withLaying Open; Bascom's Technique; Bascom’s procedure